Pengaruh penguatan positif terhadap keterampilan mengumpan bawah pada siswa sekolah menengah - Deddy Whinata Kardiyanto; Bambang Wijanarko; Wasis Himawanto (Universitas Nusantara PGRI Kediri, 2025)
Learning basic volleyball skills, particularly underhand passing, often presents challenges such as inconsistent movement execution and low student motivation. These issues highlight the need for instructional approaches that support both technical development and engagement. This study examines whether positive reinforcement can improve underhand passing performance among junior high school students. A quasi-experimental pre-test–post-test control group design was applied to 72 students aged 13–14 years, who were assigned to either an experimental or control group. Following tests of normality and homogeneity, paired and independent sample t-tests were used to analyze performance changes. The experimental group showed a 16.43% improvement, compared with 11.50% in the control group, and only the experimental group demonstrated a statistically significant gain. These findings suggest that positive reinforcement, such as verbal praise after correct arm contact or immediate acknowledgement following consistent passing repetitions, may contribute to more stable movement execution, sustained attentional focus, and greater student engagement. By addressing the limited number of experimental studies on reinforcement-based learning in volleyball passing skills, this study extends motor learning theory by providing evidence on how reinforcement supports feedback processing, movement pattern stabilization, and motivational learning environments. Practically, the results offer physical education teachers concrete guidance for integrating reinforcement-based strategies into school-based volleyball instruction.